2003
DOI: 10.1039/b303208f
|View full text |Cite
|
Sign up to set email alerts
|

The application of polymer-bound carbonylcobalt(0) species in linker chemistry and catalysis

Abstract: Carbonylcobalt(0) species have been used as linkers between alkynes and a polymer support for the first time. The alkynes may be loaded indirectly onto a phosphine functionalised polymer via their hexacarbonyldicobalt(0) complex, or directly onto a cobalt coated polymer. The alkynes have been released either as alkynes, thus providing a traceless method of immobilising alkynes, or by reaction with an alkene to generate a cyclopentenone via the Pauson-Khand reaction. The cobalt coated polymers produced during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The cobalt–phosphine complex 7 a and its alkyne complex 8 were characterised by IR spectroscopy. The IR absorptions of the carbonyl groups of the polymer‐supported complexes 7 a and 8 showed good correlation with those of [Co 2 (CO) 7 (PPh 3 )], the corresponding non‐polymer‐supported complex 4 and similar known cobalt complexes (see Figure S4 in the Supporting Information) 17c. 19, 26…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…The cobalt–phosphine complex 7 a and its alkyne complex 8 were characterised by IR spectroscopy. The IR absorptions of the carbonyl groups of the polymer‐supported complexes 7 a and 8 showed good correlation with those of [Co 2 (CO) 7 (PPh 3 )], the corresponding non‐polymer‐supported complex 4 and similar known cobalt complexes (see Figure S4 in the Supporting Information) 17c. 19, 26…”
Section: Resultsmentioning
confidence: 70%
“…We employed the TentaGel PS‐PEG (polystyrene‐polyethylene glycol) resin as it has been used as a polymer support for catalysts in aqueous media and is also compatible with organic solvents due to its good swelling ability. TentaGel®‐supported phosphine 6 was synthesised according to a reported procedure,24 and subsequently the brown phosphine–cobalt complex 7 a was prepared by mixing 6 and [Co 2 (CO) 8 ] in THF at room temperature 17c. 19 The reaction of cobalt complex 7 a supported on TentaGel with alkyne 1 (2 m M ) was carried out in aqueous HEPES buffer (pH 7.0)25 containing 0.5 % Triton X‐100.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alkyne-cobalt complex can be subsequently immobilized onto a solid-supported phosphine. It has been demonstrated that alkyne-cobalt complexes react selectively with triphenylphosphine (PPh 3 ) and solid-supported PPh 3 2223. We envisioned using an approach similar to the latter case to selectively remove the alkyne from the vast majority of native phospholipids which are washed away.…”
mentioning
confidence: 99%
“…Phosphines are good ligands for alkyne-cobalt complexes, and phosphines on polystyrene ( 18 ), Novagel ( 20 ), and silica gel were examined as potential solid supports for ligation of the alkynyl lipid cobalt complexes. For small nonpolar alkynes, polystyrene-phosphine beads worked well.…”
Section: Cobalt Complex Ligation To Solid Support and Releasementioning
confidence: 99%